Pelatihan Desain Kemasan, Branding dan Literasi Keuangan Kelompok Tani Elok Mekar Sari - Yosef Richo Adrianto; Martinus Sony Erstiawan; Darwin Yuwono Riyanto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The main objective of this service activity is to overcome the fundamental problems faced by the Elok Mekar Sari Farmer Group, namely unattractive product packaging design, weak brand identity (branding), and suboptimal financial literacy of members. The urgency of this activity is based on the urgent need to improve the competitiveness of their products in a competitive market, build a strong brand image to attract and maintain customer loyalty, and improve the efficiency of business management to ensure the economic sustainability of the farmer group in the long term. The method applied was interactive training and workshops with a participatory approach, actively involving members, with quantitative impact evaluation using Likert-scale pre-test and post-test questionnaires (N=15) on three focus areas (design, branding, finance). Evaluation results consistently concluded highly statistically significant and practical improvements in understanding, awareness, and perceived capabilities in all areas following the training. The most transformative and striking change was observed in the financial literacy aspect, which had previously been the group's weakest point. Overall, the training proved highly effective in equipping participants with essential practical knowledge and skills, providing a strong foundation for farmer groups to overcome business challenges and increase their sustainability potential going forward